Numerical and physical modelling of future Rhône Delta (Switzerland). Issue 2 (1st April 2018) - Bollaert, Erik; Mano, Vincent; Duarte, Rafael; Jaeggi, Martin
Abstract : The Rhône River on its Swiss course flows through the Lake of Geneva before traversing Geneva and continuing towards France. The river is entirely canalized upstream of the Lake of Geneva, over a length of about 160 km. Hence, a large river restoration project, the Third Rhône River Correction, is being planned for the upcoming 20-30 years. One of the first works to be realized will be the restoration of a delta estuary of the Rhône River into the lake. This delta will propose morphological diversity over a length of about 1.5 km, for a width of about 0.8 km, and will consist of a terrestrial part and a lake part. Both numerical and physical modelling have been performed to assess the morpho-dynamic potential of this delta. The morphological numerical modelling predicts evolution of the delta within a time frame of 30 years. The maritime numerical modelling shows the deformation of the delta head due to storm events on the lake, as well as the related littoral transport. The computations allowed assessing the progressive development of the delta into the lake, as well as the evolution of the terrestrial part and of a secondary river stretch. This allowed determining 3 interesting geometries to be tested on a physical model. The physical model has been constructed at an undistorted 1: 75 scale and reproduces morphology of the Rhône River and its delta with a movable bed and a movable delta. Two different materials have been mixed to simulate the sand and gravel parts of the sediment transport. Also, a wave generator has been used to reproduce storm events on the lake. This paper presents a comparison of numerical and physical model predictions of the morpho-dynamic behavior of the delta, including the influence of coastal events on the estuary dynamics.